(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Effective performance appraisal systems are crucial for improving public sector service delivery. In Tanzania, the Open Performance Review and Appraisal System (OPRAS) has been implemented to enhance accountability, yet its effectiveness in the public health sector remains inconsistent, often attributed to supervisors’ roles. This study examines the influence of specific supervisory actions—objective setting, commitment, and the administration of reward systems—on the effectiveness of OPRAS. An explanatory research design was employed, and data were collected via a structured questionnaire from a stratified sample of 310 employees across six major public health institutions in Tanzania. Data were analyzed using multiple linear regression. The results indicate that supervisors’ commitment (β = 0.298, p < 0.001) and reward systems (β = 0.348, p < 0.001) have a strong, statistically significant positive effect on appraisal effectiveness. Conversely, the effect of objective setting was positive but statistically insignificant (β = 0.124, p = 0.077). This suggests that while clear goals are beneficial, the active engagement of supervisors and the tangible recognition of performance are far more critical levers for enhancing the appraisal system’s impact. The study concludes that for OPRAS to achieve its intended goals in Tanzanian public health institutions, policy interventions should prioritize strengthening supervisory commitment and ensuring the timely and fair distribution of rewards. The findings underscore the need to move beyond bureaucratic compliance with objective-setting and focus on the motivational aspects of performance management led by dedicated supervisors.